Optimalisasi Peran Lembaga Bantuan Hukum (LBH) Medan Dalam Melindungi Hak-Hak Korban Cyberbullying - Surbakti, Dedy Suryanta; Bilqisthi, Muhammad Fardian; Chic, Sebastian Areen; Roberto, Andre Benneres (LPPM UMRI, 2025)
Cyberbullying is an activity that can damage mentally and psychologically or even take a person's life. Cyberbullying occurs because of the high intensity of human needs for the internet in fulfilling all their daily activities. Unwise use of social media is one example of cyberbullying crime. Legal Aid Institute (LBH) Medan is an organization that focuses on providing structural legal assistance for the poor, oppressed and marginalized based on human rights. Counseling is considered important considering that there will be many people who need legal aid services from LBH Medan in protecting their rights as internet users. The Faculty of Informatics Engineering of Mikroskil University conducted counseling to LBH Medan so that later LBH Medan could be more professional in handling cases around cyberbullying. This activity took place at the LBH Medan office which was attended by 5 lawyers as respondents. The method in this activity is counseling. From the results of the activity evaluation, 80% of respondents strongly agreed that this counseling was easy to understand and 100% of respondents felt that this counseling material was very useful. Based on the results of counseling, it is known that there is an increase in knowledge of respondents following counseling.